Doradztwo zawodowe jako działanie wartościowe i pożądane społecznie - Barańska, Magdalena (Pedagogika Społeczna Nova, 2023)
Vocational guidance can be very generally called a process of getting to know oneself. It is a lifelong process, inextricably linked to all the activities that an individual undertakes. Around the world, for almost a century, researchers have been trying to answer the question of why people make specific educational and professional choices. What determines success and what influences failure. The authors of the resulting theories not only answer those questions but create as well methodologies for working with a person in need of support, construct the necessary tools for this process. Over the years counseling has evolved from a very directive relationship to a partnership in which the vocational counselor has become a companion, a partner of the person being counseled. The article outlines what is career counseling, who is the counselor and why it is worthwhile to use this form of support, in an individual and social context.